The Effect of the Nanoscale Intimacy of Platinum and Acid Centres on the Hydroisomerization of Short-chain Alkanes - Morávková, Jaroslava; Pilař, Radim; Bortnovsky, Oleg; Kaucký, Dalibor; Vondrová, Alena; Rathouský, Jiri; Sádovská, Galina; Sazama, Petr (Elsevier Science BV, 2022)
This study analyses the effect of the nanoscale intimacy of Pt metal and Bronsted acid sites on the hydroisomerization of n-pentane and n-hexane using a series of zeolite/binder composite catalysts with Pt located outside or inside of the zeolite crystal and with Pt dispersed in the zeolite crystal and its vicinity on the binder. Analysis of the conversions of n-pentane and n-hexane to branched isomers and C-n <= 4 byproducts under the relevant conditions of the process showed that the highest activity is obtained for catalysts with high proximity of acid and Pt sites dispersed in the zeolite crystal together with Pt on the binder surrounding the zeolite crystals. Such an arrangement allows the hydrogenation/dehydrogenation of alkanes in close proximity to the Bronsted sites, allowing the full functionality of acid sites and limiting the diffusion of intermediate alkenes between Pt sites.
Vliv nanoměřítkové intimity platiny a kyselých center na hydroizomeraci alkanů s krátkým řetězcem
Keywords: hydroisomerization; hydrocracking; beta zeolite (*BEA); bifunctional catalysis; platinum; hexane; pentane; hydroisomerizace; hydrokrakování; beta zeolit; platina; hexan; pentan